2017
DOI: 10.4038/tar.v28i2.8194
|View full text |Cite
|
Sign up to set email alerts
|

Yield and nutritional quality potential of three fodder grasses in the Northern region of Sri Lanka

Abstract: ABSTRACT. Feeding standards of ruminant livestock could

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 6 publications
4
17
0
Order By: Relevance
“…The CF content of all fodder species was above 35%. The proximate composition of corn and sorghum are in agreement with other workers (Chaudhary et al, 2012;Heuze et al, 2016;Sarmini and Premaratne, 2017). The DM, CP and ash contents of palmyrah leaves found in the present study were in agreement with the report of Mohanajeyaluxmi (1986) and Perera (1992).…”
Section: Proximate Compositions Of Pre-ensiled Materialssupporting
confidence: 93%
“…The CF content of all fodder species was above 35%. The proximate composition of corn and sorghum are in agreement with other workers (Chaudhary et al, 2012;Heuze et al, 2016;Sarmini and Premaratne, 2017). The DM, CP and ash contents of palmyrah leaves found in the present study were in agreement with the report of Mohanajeyaluxmi (1986) and Perera (1992).…”
Section: Proximate Compositions Of Pre-ensiled Materialssupporting
confidence: 93%
“…A field study (Samarawickrama et al, 2018)in Peradeniyaat the 42 days after planting reported a lower number of leaves ( 51) with different spacing. The leaves count per plant are very important as the leaves have a higher nutritive value than the stem (Sarmini and Premaratne, 2017).…”
Section: Growth Characteristicsmentioning
confidence: 99%
“…Each plant has a specific phytochemical profile consisting of both primary and secondary metabolites that form the basis of host selection and discrimination by an insect (Del Campo et al ., 2001). For example, maize and rice plants contain similar nutritive values (Butterworth, 1963; Sarmini & Premaratne, 2017) but with distinct phytochemical profiles (Nawaz et al ., 2018; Wang et al ., 2018). These chemicals notify the foraging insects about the suitability of a plant as a food source (Renwick, 1994; Schoonhoven & van Loon, 1998), and therefore determine an insect's food choice and its subsequent performance (Chen et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%